(untitled) (Global Journal of Management and Business Research, 2018)
Employee relations is one of the key fundamental elements of organizational performance, prosperity and sustainability. Good employee relations results in a highly committed, motivated and loyal employees in the organizations. The aim of this paper is to examine the effect of employee relations on employee performance and organizational performance and at the same time identify various employee relations practices used by small organizations in Tanzania. The study adopted a cross-sectional survey research design and used a stratified random sampling technique to select a sample size of 387 respondents from selected small organizations in Tanzania. Data was collected using structured questionnaires and interviews and analyzed using descriptive statistics and correlation analysis and the results presented using tables. The findings of the study show that small organizations in Tanzania are aware of the benefits of maintaining good employee relations and correct remedial actions taken to minimize poor employee relations in the organization. The findings further indicate a positive significant relationship between employee relations and employee performance as well as between employee relations and organization performance. Moreover, the findings reveal the use of unfair labour practices in small organizations in Tanzania. The study recommends that small organizations in Tanzania should focus more on implementing fair labour practices and building effective and sustainable employee relations that will ensure their growth and survival.